Los tipos de poda y su relación con la producción de café en el Ecuador - Quezada Hidalgo, Lineida Del Rocio (Machala : Universidad Técnica de Machala, 2021)
In the world, coffee is one of the most commercialized and consumed products in all countries, therefore, it influences the economies of the main producers, generating sources of employment for millions of people. In Ecuador in recent years, coffee can stand out as one of the most outstanding products, due to its quality and acceptance in the market, in addition to taking advantage of the diversity of climate and geographical position that the country has, therefore it has been decided to strengthen knowledge and implementation of crop management. The pruning of the coffee tree is a fundamental technique of agronomic management in the crop, aimed at the formation of an adequate architecture of the plant, which facilitates the plagiotropic growth of the central branches that enhance production, as well as, favor flowering, fruiting and obtaining a high production with quality grains. In the management of pruning in coffee, three types are identified, which are: formation pruning: that modifies the plant giving an adequate structure, with a strong, robust stem and well distributed branches; phytosanitary pruning that allows to sanitize the entire plant, eliminating the parts damaged by pests, diseases or dry, twisted or torn branches; and the rehabilitation period that allows to eliminate the plant with low production or that has completed its productive cycle, making a cut at a height of 30 to 40 cm, in this way new shoots are obtained and consequently new plants.
En el mundo el café constituye uno de los productos más comercializados y consumido en todos los países, por ello, influye en las economías de los principales productores, generando fuentes de empleo a millones de personas. En Ecuador en los últimos años se puede señalar al café como uno de los productos más destacados, por su calidad y aceptación en el mercado, además aprovechar la diversidad de clima y posición geográfica que tiene el país, por tal motivo se ha optado en fortalecer el conocimiento y ejecución del manejo del cultivo. La poda del cafeto resulta una técnica fundamental de manejo agronómico en el cultivo, encaminada a la formación de una arquitectura adecuada de la planta, la cual facilita el crecimiento plagiotrópico de las ramas centrales potenciadoras de la producción, así como, favorecer la floración, fructificación y la obtención de una alta producción con granos de calidad. En el manejo de poda en el café se identifican tres tipos que son: poda de formación: que modifica la planta dando una estructura apropiada, con un tallo fuerte, robusto y ramas bien distribuidas; poda fitosanitaria que posibilita sanear toda la planta, eliminando las partes dañadas por plagas, enfermedades o ramas secas, torcidas o desgarradas; y la poca de rehabilitación que permite eliminar la planta con baja producción o que haya culminado su ciclo de producción, realizándose un corte a una altura de 30 a 40 cm, de esta manera se obtienen nuevos brotes y por consiguiente nuevas plantas.
Keywords: PODAS; CULTIVO; CAFÉ; PRODUCCIÓN